(3GdMeGjI GdbGfhfjI ddeQCI GdYGedI (B: s (3OGQSI JMdjdjI ebGQfI (B/ s - (3SeGM YHOGddg eMeO EHQGgjes; (3CMeO MSf GdHQYi (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3ef Hjf ChLg eYGfGI GdeQCI eG YGfJg HhUagG LRkAG ef GdWHbI GdYGedI(B: (3h dbO GfJRY GdYeGd YHQ eSjQI fVGdge Mbhbge GdeSdhHI(B: (3h cGaMJ GdeQCI GdYGedI MJi GYJQaJ GdEfSGfjI HMbhbgG(B: (3h HOCJ JMK GdNWi fMh GdbVGA Ydi GdJejjR VOgG(B: (3MJi CbQJ efXheI bGfhfjI cGedI dMeGjI GdeQCI GdYGedI(B: (3JTed JOGHjQ dMeGjI GdCeheI(B: (3h CNQi dQYGjI GdeSDhdjGJ GdYGFdjI(B: (3h CNQi dJfXje Yed GdeQCI(B: (3h CNQi dJMbjb GdeSGhGI h efGgVI GdJejjR VO GdeQCI ai eLGd GdYed(B. (3gPg GdefXheI gi ehVhY OQGSJi gPg(B: (3abVjI GdeQCI gi bVjI JfejI GdeLJeY HCcedg(B: (3adG JfejI h dG JbOe Ohf GfUGa fUa GdeLJeY(B: (3h bO JHfjJ ajgG ai gPg GdOQGSI efgkLG JMdjdkjG ebGQkfG(B: (3h dbO TedJ GdebGQfI bGfhf GdYed GdeUQi h bGfhf GdYed GdCQOfi h GdGJaGbjGJ h GdJhUjGJ GdOhdjI h GdYQHjI PGJ GdUdI h bO ChVMJ ai gPg GdOQGSI YfGUQ efXheI GdMeGjI GdbGfhfjI GdNGUI HGdeQCI GdYGedI(B: (3h GdeJeKdI HJOGHjQ MeGjI GdCeheI(B: (3h JOGHjQ QYGjI GdeSDhdjGJ GdYGFdjI(B: (3h JOGHjQ JfXje Yed GdeQCI(B: (3h JOGHjQ JMbjb GdeSGhGI h efGgVI GdJejjR VO GdeQCI ai eLGd GdYed(B: : (3h HjfJ eOi JhGab cd Jdc GdJOGHjQ eY eHOC GdeSGhGI(B: (3h eOi caGAI GdJOGHjQ GdJi CbQgG GdeTQYGf(B: (3GdeUQi h GdCQOfi(B: (3h Jdc GdJi CbQJgG GJaGbjGJ efXeI GdYed GdYQHjI(B: (3ebGQfkI HJdc GdJi CbQJgG GJaGbjGJ efXeI GdYed GdOhdjIs
Among the aspects of the women suffering what she suffered as a part of the working class, the workers grabbed their usurped rights through their struggle march, working women struggled until humanity recognized their rights and began urging the pace towards the elimination of discrimination against women, till a full legal system to protect working women. Where established, this system included measures to protect motherhood, family responsibilities, and measures to regulate the women employment, and other to achieve equality and to eliminate discrimination against women in the work field. This system is the subject of this study. Women's issue is the issue of community development; there are no development and no progress without half of the society. In this study I had adopted an analytical and comparative approach. The comparison included the comparison included the Egyptian labor law and the Jordanian labor law and the relevant International and Arabian conventionsand recommendations, the study was divided into an introductory chapter on justification of legal protection for working women, and the first chapter on maternity care and family responsibilities, and the second chapter on ban and organizing women's work in hard and dangers jobs and in night working, and the third chapter on equality and eliminating discrimination against working women. The study had clarified the elements of women working legal protection system, which consist of maternity protection measures, family responsibilities care measures, women employment regulation measures, and measures to achieve equality and to eliminate discrimination against women in the work filed. The study had demonstrated how each of those measures agreed with the principle of equality, and the efficiency of the measures approved by Egyptian and Jordanian Legislators, and the measures included in the ALO conventions compared to those adopted by the LLO conventions. I've reach a set of results and recommendations, which focused on the need to achieve equality for women, and understanding equality as a justified discrimination as much as a similar treatment.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2014.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3eTQhYjI Yed GdeQCI aj GdGSdGes; (3VhGHW Yed GdeQCI aj GdGSdGes; (3ELGRI GdCeheIs; (3Mbhb GdeQCI GdYGedIs; (3QYGjI GdWads; (3ELGRI QYGjI GdWads; (3GdELGRI GdhGdOjIs; (3MXQ JTZjd GdeQCI aj GdCYeGd GdTGbIs; (3MXQ GdYed Gddjdj ddeQCIs; (3MXQ JTZjd GdeQCI GdMGeds; (3MXQ JTZjd GdeQCI GdeQVYs; (3eHOC GdeSGhGI hYOe GdJejjRs; (3GdeSGhGI hYOe GdJejjR Hjf GdLfSjfs; (3eTQhYjI Yed GdeQCI aj GdGSdGes; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- 2014